Integrating local wisdom into an interactive biology e-module based on problem-based learning to develop student’s science literacy competencies - Asri Nur Rizka; Fida Rachmadiarti; Widowati Budijastuti; Herlina Fitrihidajati; Endang Susantini; Zurinawati Hamzah; Dayang Rafidah Syariff M. Fuad (University of Muhammadiyah Malang, 2026)
Background: Students’ scientific literacy remains difficult to develop when contextual learning only presents familiar examples without engaging learners in culturally meaningful, evidence-based problem solving. Local wisdom can serve as a pedagogical bridge between students’ lived environments and scientific inquiry. Objectives: This study examined the practicality and initial effectiveness of a local-wisdom-integrated interactive biology e-module based on Problem-Based Learning (PBL) for developing scientific literacy competencies. Methods: A pre-experimental one-group pre-test–post-test design involved 36 Grade 10 students. Data were collected using an implementation observation sheet, a student response questionnaire, and a 20-item multiple-choice test mapped to the OECD competencies of explaining phenomena, evaluating and designing investigations, and interpreting data and evidence. The test was content-validated by three experts. Results: All PBL phases were implemented consistently and students rated the e-module as highly practical. Learning improved across all three scientific literacy competencies, with the strongest development in evaluating investigation methods and transforming data representations. The implementation also revealed that device compatibility and formulating evidence-based hypotheses required additional scaffolding. Conclusion: Integrating local wisdom into a PBL e-module can support meaningful scientific inquiry when local practices are used to frame problems, generate evidence, and evaluate solutions. The design is potentially transferable to other local contexts, although stronger causal evidence requires controlled and multi-site studies.